Unsymmetrical Bis(thiosemicarbazone) Ligands and Their Nickel(II) Complexes: Synthesis, Characterization and Photocatalytic Activity - Rodrigo Burón; David G. Calatayud; M. A. Mendiola; Elena López-Torres (Inorganics)
The widespread use of organic dyes in industrial processes has led to a considerable release of these compounds into water systems, making the removal of organic contaminants from freshwater a pressing challenge. Photocatalysis, particularly through coordination compounds, presents a promising solution to this problem. In this study, we report the synthesis and characterization of three novel dissymmetric bis(thiosemicarbazone) ligands and their corresponding nickel(II) complexes, which have been extensively analyzed using various techniques. We evaluated the photocatalytic degradation of methyl orange by these nickel complexes, with results demonstrating that they exhibit superior efficiency compared to previously reported nickel-based complexes. Theoretical calculations reveal a correlation between the HOMO–LUMO energy gap and the energies of the involved orbitals. Additionally, with the growing demand for sustainable fuels that do not contribute to greenhouse gas emissions, molecular hydrogen stands out as a promising candidate. Given the potential of bis(thiosemicarbazone) complexes for electrocatalytic hydrogen evolution, we performed preliminary experiments to assess the ability of these nickel complexes to function as photocatalysts for water splitting. The results show that the three nickel complexes successfully generate hydrogen under the tested conditions, although further optimization is necessary to improve hydrogen production efficiency.